Evaluation of the E-Psycho-Oncological Short-Term Intervention "By Your Side" to Reduce Cancer-Related Distress: A Pilot Study - Strunk, Sven Erik; Graf, Johanna; Krakowczyk, Julia Barbara; Wieser, Alexandra; Heinen, Jana; Schug, Caterina; Jahre, Lisa Maria; Skoda, Eva Maria; Erim, Yesim; Teufel, Martin; Bäuerle, Alexander (2025)
OBJECTIVE: A large number of patients with cancer experience distress, but not all of them receive adequate psychological support. The e-psycho-oncological short-term intervention "By your Side" was developed to offer evidence-based and low-threshold support for cancer patients dealing with distress. METHODS: A longitudinal intervention pilot study was conducted from 4 March 2022 to 4 January 2023. N = 91 participants took part in the study. N = 82 completed the first module, while n = 23 successfully completed the whole intervention and were included in the final data analyses. "By your Side" consists of 16 modules based on cognitive behavioral therapy, acceptance and commitment therapy and mindfulness-based stress reduction. Differences in distress between the baseline (T0), post-intervention (T1), and follow-up (T2) were analyzed using an ANCOVA and post-hoc t-tests. Secondary outcomes (anxiety, depression, mindfulness, and self-efficacy) were also compared between measuring points, using ANOVAs and post-hoc tests. RESULTS: A significant reduction (padj = 0.014, d = 0.654) in distress from baseline (T0, M = 52.68, SD = 16.34) to follow-up (T2, M = 43.84, SD = 17.59) was observed. There was a significant decrease in anxiety symptoms and a significant increase in mindfulness and self-efficacy. The user's satisfaction (M = 28.00, range 8-32) and the usability (M = 89.57, range 0-100) of the intervention were high. CONCLUSION: The study provides preliminary evidence that the e-psycho-oncological short-term intervention "By your Side" can successfully reduce the distress of cancer patients. The high dropout rate (74.7%) must be taken into account. TRIAL REGISTRATION: German Clinical Trial Register (https://www.drks.de/search/de/trial/DRKS00036001), DRKS number: 00036001 (retrospectively registered).
CRIS-Team Scopus Importer:2025-03-14
Keywords: cancer; CBT; depression; distress; eHealth; MBSR; oncology; psycho-oncological; self-efficacy; short-term intervention